La rhétorique auto-victimiste comme stratégie argumentative dans la communication indépendantiste des panafricanistes du « Tout Sauf la France » - Aboubakar GOUNOUGO (Altralang Journal, 2021)
ABSTRACT: Among the features of the arguments of the Pan-Africanists who dedicate themselves body and soul to the Pan-African cause, there is one which is discreet, implicit or even unsuspected but which turns out to be conducive to capturing audiences in order to persuade them and to convince. This is the self-victimist rhetoric that not only intimately links the fate of Pan-Africanists to that of Africa, in a unique ethos of said and shown, but also turns out to be an effective strategy for the achievement of contact of the minds of speakers and their attendees so that the former can persuade and convince the latter. From there, the question arises for the analyst as to how does the claim of victim status by Pan-Africanists serve them as a communication strategy? How does it allow them to build a self-image for themselves and for Africa in order to attract the benevolence of their speakers and make them join their cause? It is therefore an analysis of the implications of this accusatory rhetoric of self-victimization that we will tackle in this reflection, which, for this, borrows its means of investigation from argumentative rhetoric and discourse analysis.